Efficiency of bupivacaine and association with dexmedetomidine in transversus abdominis plane block ultrasound guided in postoperative pain of abdominal surgery - Aksu,Recep (2018)
Abstract Background and objectives We aimed to evaluate the effect of bupivacaine and dexmedetomidine added to bupivacaine used in tranversus abdominis plane (TAP) block on postoperative pain and patient satisfaction in patients undergoing lower abdominal surgery. Methods Patients submitted to lower abdominal surgery were enrolled in the study. After anesthesia induction, ultrasound guided TAP block was performed. TAP block was obtained with 21 mL 0.9% saline in Group C (n = 31), 20 mL 0.5% bupivacaine + 1 mL saline in Group B (n = 31), and 20 mL 0.5% bupivacaine + 1 mL dexmedetomidine (100 µg) in Group BD (n = 31). Results Visual analog scale scores were lower in Group BD compared to Group C, at all time points (p < 0.05); it was lower in group BD than in group B at 10-24 h. In Group B, it was lower than Group C at 2-8 h (p < 0.05). Total morphine consumption was lower in Group BD compared to other groups and lower in group B than in the controls (p < 0.001). Patient satisfaction was higher in Group BD than in other groups and was higher in both study groups than in the controls (p < 0.001). Nausea-vomiting scores, antiemetic requirement, or additional analgesic administration were not significant among groups (p > 0.05). Conclusions The addition of dexmedetomidine to bupivacaine on TAP block decreased postoperative pain scores and morphine consumption; it also increased patient satisfaction in patients undergoing lower abdominal surgery. Dexmedetomidine did not have any effect on nausea and vomiting score and antiemetic requirement.